2014
DOI: 10.1037/a0036637
|View full text |Cite
|
Sign up to set email alerts
|

The detrimental effects of atypical nonverbal behavior on older adults’ first impressions of individuals with Parkinson’s disease.

Abstract: After viewing short video clips of individuals with Parkinson's disease (PD) who varied in the symptoms of facial masking (reduced expressivity) and abnormal bodily movement (ABM: including tremor and related movement disorders), older adult observers provided their first impressions of targets' social positivity. Impressions of targets with higher masking or ABM were more negative than impressions of targets with lower masking or ABM. Furthermore, masking was more detrimental for impressions of women and when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Quantitative research also has validated the source of stigma by surveying public attitudes toward PD [9] and by examining others’ impressions of PD symptoms [10-12]. Moore and Knowles reported that nearly half of survey respondents considered the disease to be stigmatizing [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative research also has validated the source of stigma by surveying public attitudes toward PD [9] and by examining others’ impressions of PD symptoms [10-12]. Moore and Knowles reported that nearly half of survey respondents considered the disease to be stigmatizing [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Tickle-Degnen et al showed that facial masking may bias health care practitioners’ views of people with PD as more depressed, less sociable, and less cognitively competent than their actual attributes [10]. Moreover, Hemmesch et al reported that higher facial masking or higher abnormal bodily movement (including tremor and related abnormal movement) of individuals with PD elicited more negative first impressions in older adult observers [11, 12]. Due to both personal beliefs and public negative attitudes embedded in our society, people with PD are likely to feel stigmatized and thus suffer from psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Caregiving for a person with PD can lead to increased stress, depression, and decreased health in CPs [911], and these effects could be compounded if the person one is caring for is less able to communicate positive emotions like gratitude and happiness [12]. Understanding how CPs’ social lives are associated with their perceptions of their partners’ facial expression could give rise to potential ways to improve quality of life and relationships in care partners and people with PD.…”
Section: Introductionmentioning
confidence: 99%
“…More LEDD use was associated with improvements in mobility and ADL subscores, which likely capture levodopa-responsive motor symptoms. Given the debilitating effects of tremor particularly on both ADLs and on stigma 27,28 , it was unsurprising that higher baseline tremor scores were associated with postoperative improvements for these subscores. A more unexpected result after unilateral DBS was that higher baseline PIGD scores were associated with less postoperative ADL improvement in the STN cohort, but more improvement in the GPi cohort.…”
Section: Discussionmentioning
confidence: 99%